POIN HUKUMAN DALAM MENINGKATKAN DISIPLIN SISWA SMA - Irlan Irlan; Rohiat Rohiat; Puspa Djuwita (UNIVERSITAS BENGKULU, 2017)
This study aimed to describe the management of punishment point that applied at Public Senior High School number one in Kepahiang Regency to the improve students’ discipline. The subjects of this study are the Principal, the deputy of principal for student affair, counselor teachers, and students. The data collection to be done by using observation, interviews, and documentation method. The data was conducted by using qualitative descriptive analysis. The results showed that the planning, organizing, actuating, monitoring and evaluation activity punishment points at Public Senior High School number one Kepahiang Regency just running well.